2018
DOI: 10.22271/tpr.2018.v5.i2.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on osmolytes and relative water content of selected rice genotypes

Abstract: Reduction in relative water content (RWC) and photosynthesis (dry matter) is a common effect of salinity stress. In the present study, 7 days old rice plants were exposed to 0 (control) and 100 mM NaCl salinity for 7 days to determine the osmolytes accumulation and relative water content (RWC) in leaves. We observed that shoot dry matter, relative water content and K + content decreased significantly with the increasing of salinity. In contrast, Na + and proline content excessively increased in the leaves of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 26 publications
(35 reference statements)
3
29
0
Order By: Relevance
“…Similar results have been obtained for sugar beet grown under 250 mM salt stress [ 60 ]. The decrease in LRWC can result in a high accumulation of salt in the rhizosphere, which impedes water uptake by the roots [ 61 ]. Studies by Yildirim et al [ 62 , 63 ] and Sayyari et al [ 64 ] found that spraying with exogenous GB and exogenous SA increased LRWC in lettuce subjected to water stress and salt stress, results which are consistent with the data shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been obtained for sugar beet grown under 250 mM salt stress [ 60 ]. The decrease in LRWC can result in a high accumulation of salt in the rhizosphere, which impedes water uptake by the roots [ 61 ]. Studies by Yildirim et al [ 62 , 63 ] and Sayyari et al [ 64 ] found that spraying with exogenous GB and exogenous SA increased LRWC in lettuce subjected to water stress and salt stress, results which are consistent with the data shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2a). Under salinity condition, the accumulation of proline showed increasing trend in rice (Polash et al 2018), Hordeum vulgare (Reza et al 2006), Pisum sativum (Ozturk et al 2012) and Trifolium alexandrinum (Abdalla 2011). Proline may act as a non-toxic osmotic solute preferentially stabilizing the structure of macromolecules and organelles (Acosta-Motos et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, another possible reason for the reduced growth rate in maize genotypes under salt stress may be associated with the reduced RWC and induced water deficit index in the leaves. In addition, closure of the stomata and further disruption of the transpiration stream as result of water deficit-induced stimulation of abscisic acid synthesis may be indirectly responsible for the reduced growth rate in the salt-stressed maize genotypes used in this study (Polash et al, 2018).…”
Section: Discussionmentioning
confidence: 99%